Workshop and Mentoring on Writing Learning Implementation Plans for Vocational Training Institutions in Bali Province - Juangsih, Juju; Dewanti, Via Luviana; Haristiani, Nuria; sugihartono, Sugihartono; Afifah, Muthi (Dimasatra, 2025)
The increasing number of internships from Indonesia to Japan provides opportunities for institutions offering Japanese language training. Based on data from the Indonesian Ministry of Manpower, 300 Sending Organizations (SO) are legally authorized to send interns to Japan. However, many Vocational Training Institutions (Lembaga Pelatihan Kerja or LPK) are managed by business operators without a background in Japanese language education. Their Japanese language training programs primarily focus on preparing candidates to pass the Japanese Language Proficiency Test (JLPT) levels N5-N3, as Japan’s Ministry of Labor requires. This results in less attention given to proper learning implementation, appropriate textbook selection, relevant evaluation methods, and other aspects of quality instruction. This community service activity (PkM) aims to transfer knowledge and provide insights to Japanese language training providers and LPK instructors, particularly on creating Learning Implementation Plans (RPP). The partners in this community service project are LPKs located in the Province of Bali. The PkM activities will be conducted through training and mentoring, with training sessions held online and mentoring sessions conducted offline.The expected outputs of this PkM activity include drafts of RPPs created by the training participants, publication of PkM results in the form of scientific articles in national journals, activity videos, presentations at national or international seminars (such as ICJLE/ICOLLITE), media publications, and intellectual property rights (HKI).